PERLINDUNGAN HUKUM DALAM TRANSAKSI DIGITAL BUDIDAYA IKAN LELE PENGENALAN UU ITE SEBAGAI UPAYA PENCEGAHAN PENIPUAN ONLINE - Yanti Sinurat, Asri Vivi; Yuma, Febby Madonna; Syahputra, Abdul Karim; Sirait, Kiki Adha (Smart Education, 2025)
Abstract: Advances in digital technology have made catfish farming transactions more efficient for MSMEs in the fisheries industry, but have also increased the potential for fraud, including identity theft, which can result in losses and undermine customer trust. Despite being a legal framework, Law No. 11 of 2008 concerning Electronic Information and Transactions remains poorly understood or implemented by MSMEs. This is exacerbated by a lack of digital literacy and the difficulty law enforcement faces in detecting fraud. With the enactment of the Electronic Information and Transactions Law and the push to improve digital education and literacy, this program aims to provide comprehensive legal protection. The objectives of this study are to categorize various forms of fraud, assess business actors' understanding of the Electronic Information and Transactions Law (UU ITE), and examine laws and regulations related to online transactions in catfish farming. Digital forensic research, along with normative and empirical legal methodologies, were used to qualitatively and descriptively assess the data. The expected outcomes are a social media-based legal education program and a legal protection model for digital micro-fisheries businesses with a Technology Readiness Level (TTL) for the use of digital forensics. Keywords: Legal Protection; Digital Transactions in Catfish Cultivation; Introduction to the ITE Law; Prevention Efforts; Online Fraud Abstrak: Kemajuan teknologi digital telah membuat transaksi budidaya lele lebih efisien bagi UMKM di industri perikanan, tetapi juga meningkatkan kemungkinan penipuan, termasuk pencurian identitas, yang dapat mengakibatkan kerugian dan merusak kepercayaan pelanggan. Meskipun merupakan kerangka hukum, Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik masih belum dipahami atau diterapkan dengan baik oleh UMKM. Hal ini diperparah oleh kurangnya literasi digital dan kesulitan penegak hukum dalam mendeteksi penipuan. Dengan disahkannya Undang-Undang Informasi dan Transaksi Elektronik dan dorongan untuk meningkatkan edukasi dan literasi digital, program ini bertujuan untuk memberikan perlindungan hukum yang menyeluruh. Tujuan penelitian ini adalah untuk mengkategorikan berbagai bentuk penipuan, menilai pemahaman pelaku usaha terhadap UU ITE, dan mengkaji peraturan perundang-undangan yang berkaitan dengan transaksi daring dalam budidaya ikan lele. Penelitian forensik digital serta metodologi hukum normatif dan empiris digunakan untuk menilai data secara kualitatif dan deskriptif. Hasil yang diharapkan adalah program edukasi hukum berbasis media sosial dan model perlindungan hukum bagi usaha perikanan mikro digital dengan Tingkat Kesiapan Teknologi (TTL) untuk pemanfaatan forensik digital. Kata kunci: Perlindungan Hukum; Transaksi Digital Budidaya Ikan Lele; Pengenalan UU ITE; Upaya Pencegahan; Penipuan Online